2018
DOI: 10.1249/jes.0000000000000149
|View full text |Cite
|
Sign up to set email alerts
|

Performance Limitations in Heart Transplant Recipients

Abstract: We hypothesize that the reduced peak aerobic power (peak VO2) following heart transplantation (HT) is due to impaired cardiovascular and skeletal muscle function, and its improvement with short-term (≤1 year) exercise training is primarily due to favorable skeletal muscle adaptations. Further, the increased peak VO2 with long-term (>2 years) training is primarily mediated by cardiac (sympathetic) reinnervation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 83 publications
0
43
0
Order By: Relevance
“…Our findings clearly demonstrate the importance of postoperative CR participation in improving functional capacity and implications of survival following HTx. Specifically following HTx, the benefits of CR involvement are widespread for this clinically unique population; including counteracting marked deconditioning and skeletal muscle weakness associated with end-stage HF, corticosteroid treatment, and surgical recovery [18,34,35,36]. Although the predictive quality of CR session attendance has not been previously reported, the increase in VO 2peak following CR in HTx patients is well-documented [15,19,20,37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings clearly demonstrate the importance of postoperative CR participation in improving functional capacity and implications of survival following HTx. Specifically following HTx, the benefits of CR involvement are widespread for this clinically unique population; including counteracting marked deconditioning and skeletal muscle weakness associated with end-stage HF, corticosteroid treatment, and surgical recovery [18,34,35,36]. Although the predictive quality of CR session attendance has not been previously reported, the increase in VO 2peak following CR in HTx patients is well-documented [15,19,20,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…One such study found a 5% lower risk of all-cause mortality or hospitalization for every 6% increase in VO 2peak , thereby highlighting the importance of even seemingly small improvements in VO 2peak on long-term clinical outcomes [7]. It should be noted, however, that despite significant functional improvements observed following HTx, VO 2peak values still remain abnormal in HTx patients compared to age-matched control subjects [34,41,42]. Further understanding of the demographic, clinical, and rehabilitative components that predict post-HTx VO 2peak values offers greater insight into the complex cardiopulmonary and peripheral adaptations occurring following HTx.…”
Section: Discussionmentioning
confidence: 99%
“…What induces the "high-intensity interval training effect" is still unclear. In the adult maintenance heart transplant population, the improved peak oxygen consumption seems to rely on mostly peripheral changes such as improved muscle strength and function [11,[14][15][16][17]. In the de novo heart transplant population, the peak oxygen consumption improvement during the first year is more complex to describe, but seems to be associated with both central and peripheral factors [10].…”
Section: Discussionmentioning
confidence: 99%
“…In the adult maintenance heart transplant population, the improved peak oxygen consumption seems to rely on mostly peripheral changes such as improved muscle strength and function. 10,[14][15][16] In the de novo heart transplant population, the peak oxygen consumption improvement during the first year is more complex to describe, but seems to be associated with both central and peripheral factors. 11 This is also reflected in the current young HITTS population where the high-intensity interval training group had a borderline significantly higher O 2 pulse (Table 2), which again by some is associated with a higher stroke volume.…”
Section: Discussionmentioning
confidence: 99%